Impact of Covid-19 infection on thyroid functions - Hanaa S. Hamed; Reda El khodary; Samah Mohamed Lotfy; Maha Mahmoud Hamed Sakr; Mohammad Walaa Saied (The Egyptian Journal of Bronchology)
Abstract Background The 2019 coronavirus illness (COVID-19) has caused significant disruption on a worldwide scale. With several recent studies observing the rise of thyroid problems in afflicted individuals, the influence of COVID-19 on thyroid function is receiving more attention. This study aims to determine the prevalence of thyroid dysfunction in COVID patients. Methods We evaluated thyroid function tests (TFTs) in 129 patients who were hospitalized to Zagazig University Hospitals with confirmed COVID-19 infection. Patients with pre-existing thyroid conditions or those on medications influencing (TFTs) were excluded. Serum levels of free thyroxine (FT4), thyrotropin (TSH), and free triiodothyronine (FT3) were measured on the first day of admission, followed by follow-up TFTs within the first six months, one year, and two years after discharge. Results We included 129 patients aged between 22 and 70 years, with 38 (29.5%) identified as male and 91 (70.5%) as female. Upon admission, (TFTs) were normal in 14.9% of patients. The findings also revealed 13.2% with subclinical hypothyroidism, 32.6% with subclinical hyperthyroidism, 6.2% with hypothyroidism, and 37.2% with hyperthyroidism. Two years after discharge, only 43.4% had normal TFTs, while 10.1% were being treated for hypothyroidism and 46.5% for hyperthyroidism. Conclusion This study emphasizes the complex interplay between COVID-19, thyroid function, and vaccination status. The results indicate that thyroid dysfunction specifically hyperthyroidism, subclinical hyperthyroidism, hypothyroidism, or subclinical hypothyroidism might be a frequent outcome for patients recovering from COVID-19, particularly in those who experienced more severe cases.